Ovarian response and embryo production of cows superstimulated with different FSH regimens and inseminated with conventional or sex-sorted spermatozoa - Folchini, Natália Picoli (2021)
A series of studies were performed to compare effects of FSH regimens on follicular superstimulation and in vivo embryo production of Holstein cows, and to evaluate the effect of SexedULTRA 4M semen from sires with distinct field fertility on in vivo embryo production. The superovulation protocol consisted of a presynchronization, followed by a superstimulation period. In D-FSH group, 300 mg of FSH were distributed over 10 decreasing doses, whereas in C-FSH group, the same amount was distributed over 10 constant doses. Insemination occurred 12 and 24 h post-GnRH, with conventional or SexedULTRA 4M semen, according to the experiments. Embryo collections were performed either on days 14 or 15. In Exp. 1, non-lactating cows underwent superovulations with crossover of FSH doses and were inseminated with conventional semen. In Exp. 2, in a 2x2 factorial arrangement, nonlactating cows underwent superovulations with crossover of FSH doses and, part of them, with crossover of SexedULTRA 4M semen, from sires classified as UF (recognized for higher fertility) or NUF (non-UF). In Exp. 3 (non-lactating) and 4 (lactating), in 2x2 factorial arrangements, cows underwent superovulations with the same FSH dose and with crossover of SexedULTRA 4M sires. In Exp. 1, 2, and 3, D-FSH provided greater follicular superstimulation, compared to C-FSH. However, in Exp. 4, the regimens were similar. Only in Exp. 2, D-FSH tended to have lower ovulatory response. Number of CL and total ova and embryo had a tendency or were greater for D-FSH, according to each experiment. Embryo characteristics were not influenced by doses, except in Exp. 1, where D-FSH produced more degenerate embryos. When data from all experiments were combined, D-FSH induced greater superstimulation and production of degenerate embryos, tended to reduce the ovulatory response, nonetheless, estrus expression and other variables were similar to C-FSH. Regarding SexedULTRA evaluation, in Exp. 2, UF sires were superior in transferable and freezable embryo production, and yielded less unfertilized oocytes, compared to NUF sires. In Exp. 3 and 4, NUF and UF sires showed similar results on embryo characteristics. Combined results indicated that UF were superior in transferable and freezable embryo production, and produced less unfertilized ova. Furthermore, progressive motility of UF sires was superior, compared to NUF. Cows that displayed estrus had greater ovulatory response, more corpora lutea, total ova and embryos, and transferable and freezable embryos (only for donors ≥ 2 structures recovered). Finally, there was no influence of number of corpora lutea during the superovulation protocol, as well as of ovulation on day zero, on ovarian response and embryo production. In conclusion, although decreasing doses of FSH were superior in follicular superstimulation, the embryo production efficiency was similar to constant doses. Finally, overall combined results indicated that UF sires were superior in embryo production, nevertheless, wide variability among bulls still exists.